Front Cover: Modified Calix[4]crowns as Molecular Receptors for Barium (ChemistryOpen 6/2018). Issue 6 (15th May 2018) - Steinberg, Janine; Bauer, David; Reissig, Falco; Köckerling, Martin; Pietzsch, Hans‐Jürgen; Mamat, Constantin
Abstract : The Front Cover shows the ability of special functionalized calix[4]crown‐6 derivatives to stably bind group 2 metals like barium. This binding mode is highly important for radiopharmaceutical applications not to lose the respective radiometal in vivo to avoid high background signals and/or false positive results and damages in other tissues. More information can be found in the Full Paper by J. Steinberg et al. onpage 432 in Issue 6, 2018 (DOI:10.1002/open.201800019 ).